A comparison study between WSDMDA and NDT methodologies using Quality Evaluation Framework - Mukhtar, M.A.O. (Institute of Electrical and Electronics Engineers Inc., 2016)
The selection of appropriate Model-Driven Web Engineering (MDWE) methodology as a tool to develop web applications has become an important issue in terms of features that need to be included in the web site. Quality Evaluation Framework (QuEF) is used specifically to evaluate MDWE methodologies and other methodologies in general. It can be used to evaluate either a well-established methodology or a new methodology in early stages of development. In this paper, by using QuEF, NDT as a well-established MDWE methodology has been compared with WSDMDA as a new methodology. The comparison has been conducted based on only Functionality quality characteristic of QuEF and three features namely Model-Driven Engineering (MDE), Web Modeling and Tool Support. Results show that WSDMDA is obtained a higher value for Web Modeling feature, while a higher value for other two features has been obtained by NDT methodology. Â© 2016 IEEE.